Mode of initiation and clinical significance of malignant rapid ventricular arrhythmias: An observational study. Issue 18 (May 2018) - Luo, Li-Hong; Wang, Jian-Ying; Chen, Xin; Lin, Jiafeng; Zhang, Ming
Abstract : Abstract: The purpose of this study was to explore the modes of initiation and clinical significance of malignant rapid ventricular arrhythmias (MRVAs). The surface 12-lead electrocardiogram (ECG) or sustained electrocardiomonitor graph was analyzed in 79 patients. All patients had at least 1 MRVA after being admitted to the hospital. According to the length of coupling interval of the initial premature ventricular contraction of MRVA, the modes of initiation of MRVA were divided into the following types: those initiated by premature ventricular contraction with short coupling intervals in patients with normal Q-T interval, and for which short-long-short sequences before MRVA precipitation were not observed; those initiated following short-long-short sequences, which were divided into 2 types according to the length of Q-T interval: a normal Q-T interval and a long Q-T interval. On the basis of the different modes of onset, treatments of MRVA were different. MRVAs have different modes of onset depending on the patients' underlying condition. Prompt recognition of the mode of onset is necessary to facilitate appropriate management. These findings could have important pathophysiologic and clinical implications.